Centellografía del riñón - Olivari, Américo; Testa, H.J.; García del Río, Hernán; Chwojnik, Abraham; Pecorini, Victorio (Comisión Nacional de Energía Atómica (CNEA), 1966)
Fil:Olivari, A.J. Comisión Nacional de Energía Atómica (CNEA). República Argentina